IMPLEMENTASI COBIT FRAMEWORK PADA PENGAUDITAN PROSES PENGEMBANGAN SISTEM INFORMASI AKUNTANSI - Djaja Perdana (Akademi Akuntansi YKPN Yogyakarta, 2009)
This research evaluated and estimated planning and organization processes of accounting information system in PT. Pendopo ITM by applicating audit activities with COBIT framework as standard. The auditing focused on accounting information system process including in planning and organisation domain by controlling activities identifying, risk-assessment, level of maturity measurement, performance indicators evaluation and goal achievement indicators evaluation with COBIT framework as standard. The research tools is an adoption result from COBIT Implementation Tool Set, COBIT Control Objectives, Maturity Model, Key Performance Indicators (KPI), and Key Goal Indicators (KGI) considering Critical Success Factors (CSF) that adapted into auditee’s organization environment. Data collecting method used the documents inspection, interview and self-assessment questionnaire for selected auditee. The result shows that planning and organisation of the information system processes in PT Pendopo ITM need optimal control, and include preventive control, detective control and corective control with improvement of the resources utilization effectiveness therefore this guarantee organization’s objectives achievement.Keywords: Audit, COBIT Framework, Internal Control, Risk Factor, Maturity Level, Performance Indicator, Goal Indicator, Critical Success Factor